Austrian theory and economic organization : reaching beyond free market boundaries - Nell, Guinevere Liberty, 1976; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Austrian Economic Perspectives on Market Organization is a collection of essays by economists and political scientists, each with an interest in evolutionary cultural change.
Keywords: Austrian school of economics; Free enterprise; Institutional economics; Socialism